(untitled) (Bangladesh Pharmaceutical Journal, 2015)
The present study was designed to investigate the effects of combination of Nigella sativa oil and pioglitazone on long-term alloxan-induced diabetic rats. In short-term (two weeks) alloxan-induced diabetic rats, N. sativa oil (NSO) reduced significant amount of glucose in blood, TC, TG and LDL-C and increased significant amount of HDL-C compared to diabetic rats. However, pathological changes of pancreass Islets of Langerhans were observed after long-term (four weeks) induction of alloxan in rats. Administration of NSO recovered Langerhans cells from shrinkage whereas pioglitazone displayed slight recovery. But the combination therapy showed complete recovery of Langerhans cells as compared with diabetic rats. Combination of drugs significantly reduced the TC, TG and LDL-C level as well as increased significant amount of HDL-C level to the normal level. Combination also increased DPPH free radical scavenging activity compared with diabetic rats. The results suggest that treatment with combination therapy was more effective than mono-therapy for preventing diabetes as N. sativa oil potentiates the effects of pioglitazone on long term alloxan-induced diabetic rats. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22296 Bangladesh Pharmaceutical Journal 16(2): 143-151, 2013